Non-surgical treatment of strabismus in children: a review of recent advances - Shulan Huang; Xuemei Zhong; Chanjuan Quan; Mingwen Zhang (Frontiers in Medicine)
Pediatric strabismus is a progressive condition that, in the early stages, presents as either esotropia or intermittent or constant exotropia when both eyes focus on the same target. If not promptly addressed, the child’s ocular accommodative convergence and fusion abilities will gradually weaken, ultimately affecting visual function and causing various inconveniences in daily life and learning. For children with mild strabismus, those who are young, have poor cooperation, or are awaiting surgery for a long time, non-surgical treatment is a good option. It offers high safety, ease of use, and has certain effects in alleviating strabismus symptoms and improving visual function. However, there are multiple non-surgical treatment options, and currently, clinical practice lacks clear consensus on which approach is best. The choice and implementation of treatment methods still need to be determined based on the specific situation, such as the child’s age and type of strabismus. In recent years, with the deepening of ophthalmological research, non-surgical treatment methods have been enriched, including a combination of visual training, occlusion therapy, and corrective glasses, which have shown certain clinical effects. This article will review the non-surgical treatment options for pediatric strabismus, explore current research progress, and discuss future development directions.